Characteristic, Levels of lead in the blood, and hypertension of Workers Batteries Home Industry at Talun Village Sukodadi District Lamongan Regency - Lian Dwi Fibrianti; R. Azizah (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: Lead  (Pb) is one  of the pollutants  that can cause hypertension. The objectives of this study  were  to analyze characteristic, levels  of Lead (Pb) in blood  and hypertension at home industry workers  batteries.  This research was an observational descriptive studies and used cross-sectional approach. Data obtained from interviews, questionnaires, and observation. Measurement of blood  lead used Atomic Absorption Spectrophotometer and blood  pressure measurements used a tensimeter. Samples were selected by total population of 10 workers  batteries  home industry. The results  of the research that most workers  age is less  than 30 years was 50%, the worker men  was 60%, workers  who have a habit of smoke was 30%, Pb levels  in the blood  of workers  30% above the standards set by ATSDR (1999) < 10 Î¼g/dL,  and 40% of workers  have hypertension. Cross-tabulation showed  that workers  who have hypertension that workers  aged 31–40 years (50%), workers  with employment â‰¤ 5 year period  (40%), male workers  (66.7%), workers  who was smoke (100%), workers  with no history of hypertension and diabetes (40%) and workers  who  have  levels  of lead (Pb) in the blood  > 10 Î¼g/dL (100%). Advise  the workers  to reduce cigarette  consumption and wear personal protective equipment such as masks, gloves and boots while they work to reduce exposure of lead (Pb).Keywords: characteristic of workers,  levels  of lead (Pb) in the blood, hypertension, workers  home industry batteries